KESALAHAN PEMAKAIAN BAHASA INDONESIA DALAM SURAT RESMI TULISAN SISWA SMA YPK TABERNAKEL NABIRE - Yikwa, Piter; Saddhono, Kundharu; Suryanto, Edy (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study aims to identify errors in the use of language in writing official letter to students SMAYPK Tabernakel Nabire, in the year 2017/2018. The research method used is qualitative research method with document analysis technique. The sample of the research is the writing of official letter of grade XII of SMA YPK Tabernakel Nabire. Sampling technique with purposive sampling technique. Source of data used in the form of the result of writing official letter of class XII students of YPK School Tabernakel Nabire. The result of this research is description about error of usage of Indonesian language in writing of official letter: mistake of language in writing of official letter there are 2 factors that is, morphology factor of syntax and spelling factor. The form of the language error is: 1) the error of writing letterhead, 2) writing letter address errors, 3) misconduct writing, 4) raw writing error, 5) mistakes writing date of letter making, 6) mistake of writing of opening letter, 7) mistake of the contents of the letter, 8) error writing letter number. 9) mistake writing address of letter agency, 10) mistake of writing cover letter. Based on the results of the study declared that the ability of writing official letters to students is still low. Improvements that can be taken is to improve the internal and external processes in learning Indonesian especially writing materials on YPK high school students Tabernakel Nabire.